2013
DOI: 10.3109/09513590.2012.738725
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated administration of methotrexate (MTX) on rat ovary: measurement of serum antimullerian hormone (AMH) levels

Abstract: MTX administration did not cause a statistically significant change between pretreatment and final serum AMH levels in rats. There was no decrease in AMH levels indicating a decrease in ovarian reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…As a folic acid antagonist and inhibitor of DNA synthesis, MTX functions by targeting actively proliferating cells, and in the case of an ectopic pregnancy, impedes further growth of the fetal cells. However, the impact of MTX on other dividing cells, such as oocytes and granulosa cells, is unclear [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a folic acid antagonist and inhibitor of DNA synthesis, MTX functions by targeting actively proliferating cells, and in the case of an ectopic pregnancy, impedes further growth of the fetal cells. However, the impact of MTX on other dividing cells, such as oocytes and granulosa cells, is unclear [7].…”
Section: Introductionmentioning
confidence: 99%
“…Only one epidemiological study showed that the pregnancy rates of multiple dose MTX were not different from other treatments of EP. Although various studies have attempted to evaluate the effect of single dose MTX on ovarian reserve, there is only one experimental study to evaluate the effect of multiple dose MTX on ovarian reserve with only measuring AMH levels but without control group [12]. Benian et al displayed that there was no significant difference in final AMH levels after multiple dose MTX protocol.…”
Section: Resultsmentioning
confidence: 99%
“…AMH was used as a useful biomarker to show ovarian reserve after MTX administration for EP [2]. A recent study in a rat model suggested that MTX administration in repeated doses did not decrease AMH levels [12].…”
Section: Introductionmentioning
confidence: 99%
“…Methods used to determine the ovarian reserve include a primordial follicle count, the amount of gonadotropins and the level of anti-Müllerian hormone. 5 However, the occurrence of pregnancy is the best clinical parameter illustrating the ovarian reserve and the fertility of a female.…”
Section: Introductionmentioning
confidence: 99%